PECULIARITIES OF THE ORIGIN OF PROVERBS AND SAYINGS AND THEIR PRIMARY SOURCES - Idiyeva Lola Ismatovna (International Engineering Journal For Research & Development, 2020)
As we know proverbs and sayings provide an excellent opportunity to get acquainted with the life and culture of the people for whom the given language is the native one and convince us that different peoples may have the same views and moral values. The article is about the peculiarity of the origin of proverbs and sayings is that they originated from the traditions, customs and beliefs of the English people, and that they were created on the basis of various realities and facts of English history.